Pearls And Pitfalls of Keratoplasty to Achieve and Optimal Visual Function: A Case Report: Poster Presentation - Case Report - Resident - Askary, Fadel; Solahudin, Alie (Majalah Oftalmologi Indonesia, 2023)
Introduction : Keratoplasty, also known as corneal transplant, is a surgical procedure in which a damaged or diseased cornea is replaced with a healthy donor cornea. One of the common reasons for performing this procedure is to restore vision in people with a leukoma eye. Leukoma, also known as corneal opacification, is a condition in which the cornea becomes cloudy or opaque, leading to impaired vision or even blindness. This case will explain keratoplasty procedures for treating leukoma, the benefits and risks of the surgery, and the postoperative care required for a successful recovery. Case Illustration : A 49 years old Female diagnosed with Leukoma due to her symptoms, signs, and examination with VOD: 1/60 ph (-) and VOS : 6/7.5. The patient then underwent keratoplasty surgery. 7th day post operation, Corneal Graft had 16 interrupted sutures with minimal edema. VOD 6/60 and Intra ocular pressure on the right eye was 13.1 mmHg. Oral and topical corticosteroids Continued and planned to taper off gradually. Discussion : The success of the procedure depends on several factors, including the cell count of donor, determining high/low risk patients, Intraoperative, and the postoperative care provided. Topical corticosteroids remain the mainstay to prevent immunological graft reactions. Regular evaluation of the graft is important as the risk of rejection occur up to years. Conclusion : Keratoplasty has proven to be an effective treatment option for individuals with a leukoma eye. The procedure can significantly improve visual acuity and quality of life for these individuals.